Profile of SCCmec types in clinical isolates of methicillin-resistant Staphylococcus aureus (MRSA) in a hospital in Southern Brazil.Perfil dos tipos de SCCmec de isolados clínicos de Staphylococcus aureus resistentes a meticilina em um hospital do sul - Batista, Bruna Gerardon; Alves d' Azevedo, Pedro (Journal of Health & Biological Sciences, 2016)
Methicillin-resistant Staphylococcus aureus (MRSA) is anopportunistic pathogen that affectspublic health representing the most common infections related to health care and community. MRSA infections are classified as health care-associated MRSA (HA-MRSA) and community-associated MRSA (CA-MRSA) defined by the bacteria genetic profile. This study conducts a molecular characterization of eighty-one MRSA isolates from a hospital in Porto Alegre, RS, Brazil, in a period from January to June of 2012. A multiplex PCR was performed to determine the SCCmec types. From the 81 isolates, 24 (30%) were type I, 10 (12%) type II, 21 (26%) type III, 4 (5%) type IVa, 12 (15%) isolates were type IVc, 1 isolate was type I and IVc (1%) and 1 was type III and IVc (1%) simultaneously, while non-typable isolates corresponded to 8 isolates (10%). However most of the isolates were carrying SCCmec types related to HA-MRSA, the results reveal a change in the epidemiology, considering the decrease of the incidence of SCCmec type III and the increase of isolates being typed as SCCmec I.